Study of radiological findings in papilledema - Meena, Vandana; Sharma, Unnati (International Journal of Medical Research and Review, 2016)
Background: Early recognition of papilledema and elevated ICP is of paramount importance for ensuring restoration of vision. Papilledema, frequently occurs in the setting of increased ICP and in a variety of medical conditions, including pseudotumorcerebri, sinus thrombosis, intracerebral hemorrhage, frontal lobe neoplasms, and Chiari malformation.the primary role of imaging in the diagnosis of idiopathic intracranial hypertension (IIH) has been to exclude other conditions that can cause increased intracranial pressure (ICP) and papilledema. Material & Methods: The present study is a non randomized prospective case series being conducted in the 50 patients with disc edema/papilledema attending OPD and referred from other departments to DEPARTMENT OF OPHTHALMOLOGY, Gandhi Medical College and associated Hamidia Hospital, Bhopal from January 2013- December 2014, All patients underwent a complete medical evaluation including careful history taking, ophthalmic examination, Investigations includes MRI Scan was done in Radiology as well neurology reference was taken from Neurosurgery department, Hamidia Hospital, G.M.C. Bhopal. Result: In radiological study ICSOL is observed in 70.58% cases followed by 11.76% cases of sinusitis followed by 5.88% case each venous thrombosis,demyelination and infarction. Conclusion: Early recognition of papilledema and elevated ICP is of paramount importance for ensuring restoration of vision. Newer advanced MR imaging techniques such as fMRI and DTI may prove useful in the future to assess the potential effects of papilledema on retinal and visual pathway integrity.